Neutrophil-to-Lymphocyte Ratio and Covid-19 Symptom-based Severity at Admission - M. Fuad; Amaylia Oehadian; Delita Prihatni; Marthoenis Marthoenis (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Increased Neutrophil-to-Lymphocyte Ratio (NLR) is an independent risk factor for mortality in Covid-19 patients and is considered as an early warning sign of Covid-19 severity. This study aimed to observe the differences in NLR at admission between patients with mild, moderate, and severe symptoms of Covid-19 treated in a referral hospital in Banda Aceh, Indonesia.Methods: A total of 114 patients with Covid-19 admitted to a referral hospital in Banda Aceh, Indonesia, during March–September 2020 were included in this study. Demographic information and baseline laboratory data, including the NLR, were collected. Descriptive and inferential statistics were used to analyze the data. Results: The median NLR at admission was higher among patients with moderate to severe symptoms than those with mild symptoms [6.54 (2.80–97.00, IQR 4.81–9.44) vs 2.27 (0.79–5.07, IQR 1.43-2.98), p <0.001]. Covid-19 patients who died had a higher NLR than those who survived [10.88 (4.17–47.50, IQR 7.00–15.17) vs 6.15 (2.80–97.00, IQR 4.63–8.50), p 0.02]. Patients with moderate-severe symptoms had an initial NLR of 4.63–8.50 and decreased to 2.75–5.43 at the end of the treatment had a greater chance of survival. There was an increased probability of death in patients with moderate-severe symptoms whose initial NLR was 7.00–15.17, which was then elevated to 14.33–23.25.Conclusion: Different NLR at admission is seen among Covid-19 patients with mild and moderate-severe symptoms, leading to significantly different outcomes. The NLR can be used as a simple parameter to determine the severity of the disease and predict the outcome of Covid-19 patients.